(untitled) (Conference on English Language Teaching, 2024)
In the current era of globalization, the importance of developing listening skills in learning English in elementary schools is increasing. This is due to the increasing cross-cultural exchange and the need for multilingual communication in an increasingly interconnected global environment. This explorative case study examines the use of fairy tales and folktales to develop listening skills in English language learning in elementary schools. Data for this study was collected through interviews conducted using a semi-structured approach with two English teachers who teach in two elementary schools in Central Java, Indonesia. This research used a qualitative case study approach to analyze the data. The results show that fairy tales and folktales can help develop English listening skills among primary school students in Indonesia. However, there are some challenges in implementing fairy tales and folktales as a means to develop listening skills in primary school students such as the non-integration of these methods into the curriculum, and challenges in material selection. The implications are discussed in this study.